Emergency Medicine and Trauma - Karcioglu, Ozgur; Günalp Eneyli, Müge (IntechOpen, 2019)
From prehospital evaluation to management in the emergency department,"Emergency Medicine and Trauma" provides easily accessible information on the evaluation, diagnosis, and management of trauma care. Recognition of the multidisciplinary nature and complexity of trauma care, especially the philosophy of a teamwork approach, must be an integral part of trauma management. To help make logical diagnoses and treatment plans , you will learn: The use of a structured and prioritized approach to critically ill and injured patients according to the clinical need and assessment of acuity level; How to establish resuscitation (management) priorities in a multiply injured patient; How to demonstrate the ability to adopt a holistic (multidisciplinary, biopsychosocial) approach to trauma patients. The role of the emergency department and its staff in major incidents, to understand planning and be prepared for major incidents. This book is designed not only for emergency medical providers but also for medical students.